Enhanced photoluminescence and photoactivity of plasmon sensitized nSiNWs/TiO2 heterostructures - Yenchalwar, Sandeep G.; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V. (Physical Chemistry Chemical Physics, 2014)
A light sensitive wide band gap radial heterojunction between TiO2 and nSiNWs sensitized by gold nanoparticles is reported. The surface plasmon of AuNPs influences the optical and photocurrent properties of the heterojunction considerably. Improvement in the band gap emission of TiO2 has been found at the expense of defect radiation. Excitation of AuNPs deposited on nSiNWs/TiO2 by light irradiation shows a wavelength-dependent photocurrent due to the increased photoactivity of the heterojunction.